The Impact of Parenting Avoidance (IPA): Scale Development and Psychometric Evaluation Among Parents of Transgender Youth - Haley R. Hedrick; Stephanie V. Caldas; Danielle N. Moyer (Behavioral Sciences)
Parental support and acceptance are strong protective factors for better mental health outcomes among transgender and gender diverse youth. Psychological inflexibility, specifically in the role of parenting, or “parenting inflexibility”, refers to an over-reliance on avoidance strategies at the expense of parenting values. Parenting inflexibility may be related to parental support, making it a useful target of intervention for parents of transgender youth. The aim of the present study was to develop a brief clinically useful measure of parenting inflexibility based on a synthesis of existing measures and to evaluate the psychometric properties across two study populations. Study 1 used exploratory factor analysis to examine this measure among parents in the general population recruited using MTurk. Study 2 used confirmatory factor analysis to examine the measure among parents of transgender youth recruited from a clinic. The final measure, the Impact of Parenting Avoidance (IPA) scale, is a one-factor 7-item measure of parenting inflexibility that is easy to administer and interpret in a pediatric health setting. The resulting measure demonstrated acceptable reliability, and it was significantly correlated with important outcome variables, such as negative parenting practices and lower perceived parental support among transgender and gender diverse youth.